Fourth season: Editorial - Zúñiga Antón, María (Geographicalia, 2023)
Several generations have passed from the 20 pesetas that the first issue of Geographica cost until the free distribution of its contents in its 75th edition. During that time Geographicalia has evolved defining its own personality: being an open scientific space to all geographical matters, nurturing new researchers and relying on what is close to us to reach as far as possible. In this editorial, I invite you to join me in a journey through the 46 years of Geographicalia’s history to explain how we have shaped its present and, hopefully, contributed to its future.